2018
DOI: 10.1080/1331677x.2018.1456357
|View full text |Cite
|
Sign up to set email alerts
|

The role of Chinese investments in the bilateral exports of new E.U. member states and Western Balkan countries

Abstract: This paper explores the economic relations between China and new E.U. member states and Western Balkan countries. China is an important trade partner for these countries, but in recent years the cooperation has been extended to include Chinese foreign direct investments (F.D.I.) inward investment. Using the Poisson pseudomaximum likelihood (P.P.M.L.) method to estimate a gravity model of bilateral trade, this study analysed the export flows of these countries as a function of total inward F.D.I. and Chinese F.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 29 publications
0
13
0
1
Order By: Relevance
“…estimator to estimate the gravity model of F.D.I. flow because there are some zero-valued observations and heterogeneity issues (Santos Silva & Tenreyro, 2006;Westerlund & Wilhelmsson, 2011;Jacimovic, Mitrovi c, Bjeli c, Tianping & Rajkovic, 2018). Thus, Equation (1) can be augmented to include traditional gravity variables, institutional quality and business environment indicators in this study.…”
Section: Methods Of Analysismentioning
confidence: 99%
“…estimator to estimate the gravity model of F.D.I. flow because there are some zero-valued observations and heterogeneity issues (Santos Silva & Tenreyro, 2006;Westerlund & Wilhelmsson, 2011;Jacimovic, Mitrovi c, Bjeli c, Tianping & Rajkovic, 2018). Thus, Equation (1) can be augmented to include traditional gravity variables, institutional quality and business environment indicators in this study.…”
Section: Methods Of Analysismentioning
confidence: 99%
“…Šohinger et al (2006) start from the theory that FDIs are essential for the competitiveness of the economy by applying adequate fiscal and monetary policies. Jadhav (2012) found that in BRICS (Brazil, Russia, India, China & South Africa) economy in the period 2002-2009 traditional economic determinates are more important than institutional and political determinants of FDI (Jacimovic et al, 2018). Nandi (2012), researching the same countries, found out that India is the only country among the respondents who did not regain their FDI results after the crisis.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Focusing on the Machinery and transport equipment, Gheorghe and Simion (2018) find that a high percent of the exports in this area (85%) are influenced by the imports of the same goods and the FDI directed here. Jacimovic et al (2018) is more specific and finds that an increase in bilateral exports of the new EU and Western Balkans countries is enhanced by larger flows of foreign direct investments from China. However, Chinese exports could have a double effect.…”
Section: Literature Reviewmentioning
confidence: 99%